2017
DOI: 10.1159/000479938
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Dialysis Patients with Restless Legs Syndrome: A 15-Year Follow-Up Study

Abstract: Background: Restless legs syndrome, also known as Willis/Ekbom disease (RLS/WED), is a sleep-related, sensorimotor disorder with a high prevalence among end-stage renal disease (ESRD) patients undergoing haemodialysis (HD) (about 15-40%). Whether RLS/WED in uremic patients influences cardiovascular morbidity and mortality remains a matter of controversy. The aim of this study was to evaluate the relationship of RLS/WED and mortality in a population of chronically dialyzed patients. Method: In 1996, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
12
2
Order By: Relevance
“…Similarly, the mortality rate was not influenced by gender ( p = 0.15) and even more importantly by RLS severity ( p = 0.11). In addition, the study by Baiardi et al [7] revealed no difference among the causes of death between the 2 groups; this is in contrast to previous studies linking RLS to cardiovascular diseases [5] . The studies by Stefanidis et al [6] and Baiardi et al [7] clearly suggest that mortality in HD patients is not influenced by the presence of RLS/WED, as they provide no clinical evidence linking uremic RLS/ WED to cardiovascular mortality.…”
contrasting
confidence: 61%
See 3 more Smart Citations
“…Similarly, the mortality rate was not influenced by gender ( p = 0.15) and even more importantly by RLS severity ( p = 0.11). In addition, the study by Baiardi et al [7] revealed no difference among the causes of death between the 2 groups; this is in contrast to previous studies linking RLS to cardiovascular diseases [5] . The studies by Stefanidis et al [6] and Baiardi et al [7] clearly suggest that mortality in HD patients is not influenced by the presence of RLS/WED, as they provide no clinical evidence linking uremic RLS/ WED to cardiovascular mortality.…”
contrasting
confidence: 61%
“…In addition, the study by Baiardi et al [7] revealed no difference among the causes of death between the 2 groups; this is in contrast to previous studies linking RLS to cardiovascular diseases [5] . The studies by Stefanidis et al [6] and Baiardi et al [7] clearly suggest that mortality in HD patients is not influenced by the presence of RLS/WED, as they provide no clinical evidence linking uremic RLS/ WED to cardiovascular mortality.Considering the discordant literature on the mortality risk in uremic RLS patients and the fact that cardiovascular disease is the number one cause of death in HD patients, the recent evidence by Baiardi et al [7] provides important data that will inform the design of the next prospective Disorders of the brain are becoming more prevalent and are both threatening quality of life as well as creating major challenges for the national health systems. Restless legs syndrome (RLS; or Willis/Ekbom disease) is one of the most common neurological disorders associated with significant personal, social and economic burden.…”
contrasting
confidence: 61%
See 2 more Smart Citations
“…A 15‐year follow‐up of 128 HD patients found that the 47 subjects with restless legs syndrome did not have a subsequent increase in their mortality rate …”
mentioning
confidence: 99%